Associations between per- and polyfluoroalkyl substance exposure and the prevalence of myopia in adolescents: the mediating role of serum albumin - Xuewei Li; Xiaodong Chen; Yixuan Zhang; Tonglei Zheng; Lvzhen Huang; Yan Li; Kai Wang (Environmental Health and Preventive Medicine)
Background: The objective of this study was to investigate the potential link between myopia in adolescents and exposure to per- and polyfluoroalkyl substances (PFASs). Methods: This investigation included 1971 subjects with accessible PFAS level data, myopia status, and associated variables from four cycles of the National Health and Nutritional Examination Survey (NHANES). The investigation focused on specific PFAS compounds found in the serum, including perfluorohexane sulfonate (PFHxS), perfluorononanoic acid (PFNA), perfluorooctanoic acid (PFOA), and perfluorooctane sulfonic acid (PFOS), chosen for their frequent detection. Owing to the skewed nature of the PFAS level data, the PFAS levels were log-transformed (Ln-PFAS) prior to analysis. Logistic regression, restricted cubic spline modeling, subgroup analysis, and sensitivity analysis were used to examine the associations between exposure to PFASs and the onset of myopia. Results: PFOA levels were significantly associated with myopia risk (OR: 1.33; 95% CI: 1.05–1.69; P = 0.019). More specifically, with respect to the first quartile, the second quartile (ORQ2: 1.69; 95% CI: 1.16–2.46; P = 0.007), third quartile (ORQ3: 1.45; 95% CI: 1.03–2.03; P = 0.035), and highest quartile (ORQ4: 1.58; 95% CI: 1.12–2.21; P = 0.010) of participants presented with increased myopia risk. Mediation analysis revealed that PFOA and myopia risk were partially mediated by serum albumin (ALB), with a mediation percentage of 22.48% (P = 0.008). A nonlinear inverted U-shaped relationship was identified between the level of PFOA and myopia risk (P for nonlinearity = 0.005). Conclusion: Our findings suggest a potential link between exposure to PFOA and the likelihood of myopia development in young individuals and a mediating effect of serum ALB on this relationship. Notably, PFOA was identified as a key PFAS significantly contributing to the observed link between PFAS exposure and myopia risk. The potential threat of PFOA to myopia should be examined further.